(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: Cervical cancer remains a major cause of cancer deaths among females in low and middle-income countries. Local survival studies are crucial for assessing overall management effectiveness, as they reflect the level of care provided and awareness among the population about screening and early diagnosis. Objectives: To analyze disease-free survival (DFS) among patients treated for cervical cancer and investigate clinical, management, and outcome-related independent factors associated with survival. Methods: A retrospective study was conducted on 393 cervical cancer patients from January 2014 to 2020 at the Gynecological Oncology Department of the National Institute of Cancer Research and Hospital (NICRH), analyzing demographic and clinical data, tumor characteristics, treatment options, and outcomes, including recurrence, as predictors of survival. Results: Three hundred ninety-three patients included in this study. The mean average age was 49 years, range 28-85 years. Total follow-up times(months), mean 38; range (6-108) months. Among them 61% were postmenopausal, with a majority of women having a parity of 59% and an average marriage age of 14.93±3.95. The most common presenting symptom was irregular bleeding, with 62.8% of patients being illiterate. Tumor characteristics included FIGO stage I, II, and III, with squamous cell carcinoma being the most common histopathological type. Patients received initial surgery (21.6%), radiotherapy (74%), and palliative care (4%). The mean duration of follow-up (DFS) was 2.20 years in <24 months and 3.35 years in >24 months. Residual disease and recurrence were 6.4% and 30.5%, with local recurrence being the most common (22.6%) and liver being the most common site of distal recurrence (38.3%). Survival was independently associated with age, grade II, and FIGO stage III. Conclusion: Age, grade, and FIGO clinical stages adversely affect the overall survival of cervical cancer patients. J Bangladesh Coll Phys Surg 2025; 43: 25-31